IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2021 TENTANG RETRIBUSI DAERAH DI PASAR JATIBARANG KABUPATEN BREBES - Rizki, Azam Mulyana; Pazqara, Emiraldo Win (Majalah Ilmiah Dinamika Administrasi (MIDA), 2024)
The formulation of the problem proposed is: How to Implement Regional Regulation Number 4 of 2021 concerning Regional Levies at the Jatibarang Market, Brebes Regency. The aim of this research is to describe and explain the implementation of Regional Regulation Number 4 of 2021 concerning Regional Levies at the Jatibarang Market, Brebes Regency. The research method used in this research is descriptive qualitative. The model for determining informants uses Purposive Sampling techniques with the research targets being market managers, levy officers and market traders. Based on the discussion of the results of this research, several conclusions can be drawn: (1) Aspect of level of compliance: In this aspect, implementation has not been effective, because many traders pay their levies under the regional regulations. (2) Smoothness Aspect: In terms of smoothness, it has not gone well because there are still many traders who deliberately do not pay fees. (3) Aspect of Performance and Impact: This aspect has not been implemented effectively because the retribution target has not been achieved.The implications are used to improve the implementation of Regional Regulation Number 4 of 2021 concerning Regional Levies at the Jatibarang Market, Brebes Regency; (1) Jatibarang Market Managers should carry out re-socialization regarding market levies. (2) Jatibarang market managers should improve the physical infrastructure of the market so that it becomes more comfortable. (3) Market traders must further improve their service and be friendly to consumers.